Innovation and adaptation in advocacy organizations throughout the digital eras. Issue 2 (2nd April 2020) - Dennis, James; Hall, Nina
ABSTRACT: This special issue explores how digitally-native advocacy organizations evolve and whether they influence the organizational norms of other NGOs and advocacy groups. The volume offers three contributions to the literature on digital advocacy groups. Firstly, we argue that different periods of 'internet time' influence the tactics, strategies, and structural form of political organizations. Secondly, we examine different ways that organizations empower members and/or the broader public to make decisions using digital technology. Thirdly, we trace the diffusion of digital engagement practices, as well as how legacy advocacy groups have adapted these practices. Finally, we provide an agenda for future research. Specifically, research is needed on changes in digital organizing in Africa, Asia, and Latin Amerca, and center-right and far-right advocacy organizations. Further work is also necessary to identify the conditions that lead to innovation in digital advocacy.